The RNA m6A Methyltransferase PheMTA1 and PheMTA2 of Moso Bamboo Regulate Root Development and Resistance to Salt Stress in Plant - Wang, Huihui; Wang, Huiyuan; Jia, Yue; Jin, Xiaoxia; Wu, Hongwei; Yang, Siyu; Zhao, Liangzhen; Zhang, Hangxiao; Gu, Lianfeng (Plant, cell and environment, 2025)
ABSTRACT As the most prevalent RNA modification in eukaryotes, N6‐methyladenosine (m6A) plays a crucial role in regulating various biological processes in plants, including embryonic development and flowering. However, the function of m6A RNA methyltransferase in moso bamboo remains poorly understood. In this study, we identified two m6A methyltransferases in moso bamboo, PheMTA1 and PheMTA2. Overexpression of PheMTA1 and PheMTA2 significantly promoted root development and enhanced salt tolerance in rice. Using the HyperTRIBE method, we fused PheMTA1 and PheMTA2 with ADARcdE488Q and introduced them into rice. RNA sequencing (RNA‐seq) of the overexpressing rice identified the target RNAs bound by PheMTA1 and PheMTA2. PheMTA1 and PheMTA2 bind to OsATM3 and OsSF3B1, which were involved in the development of root and salt resistance. Finally, we revealed the effects of transcription or alternative splicing on resistance‐related genes like OsRS33, OsPRR73, OsAPX2 and OsHAP2E, which are associated with the observed phenotype. In conclusion, our study demonstrates that the m6A methyltransferases PheMTA1 and PheMTA2 from moso bamboo are involved in root development and enhance plant resistance to salt stress. Summary statement This study reveals that m6A RNA methyltransferases, PheMTA1 and PheMTA2, from moso bamboo play a critical role in regulating root development and enhancing salt tolerance in rice by the identification of target RNAs associated with resistance‐related genes. The findings provide novel insights into m6A‐mediated regulation of stress responses and developmental processes, addressing a gap in understanding the functional roles of m6A modification in plants.